Distance Learning Solutions: Tools Used in Online Lessons - Khalilova, Aysel Zahid (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The goals of distance education in higher institutions were clear for many years. Nowadays, owing to the global pandemic situation, higher educational institutions (HEI) have had to transition from conventional teaching modes to online modes. Although many top-ranked universities were prepared for this situation, others suffered, since their distance education department existed only in name; their activities were passive. However, COVID-19 provided an opportunity for them to think deeply about their next steps. In general, distance learning is an effective way of attracting adult learners. Furthermore, these learners desire a higher level of flexibility. This article is based on the theoretical models essential to long-term plausibility and viability in the field of teaching practice. To evaluate the challenges and problems arising during online learning, the author has briefly reviewed all the contributions made to this field in the 21st century. In addition, the paper suggests tools and facilities for teachers and instructors in order to facilitate effective communication between teachers and students, both in and out of the virtual classroom. Researchers, post-graduate students and other readers will be able to use this paper to explore and exploit further modifications of research opportunities in this field.